Calmodulin variants associated with congenital arrhythmia impair selectivity for ryanodine receptors - Dal Cortivo, Giuditta; Marino, Valerio; Bianconi, Silvia; Dell'Orco, Daniele (Frontiers in Molecular Biosciences, 2023)
Among its many molecular targets, the ubiquitous calcium sensor protein calmodulin (CaM) recognizes and regulates the activity of ryanodine receptors type 1 (RyR1) and 2 (RyR), mainly expressed in skeletal and cardiac muscle, respectively. Such regulation is essential to achieve controlled contraction of muscle cells. To unravel the molecular mechanisms underlying the target recognition process, we conducted a comprehensive biophysical investigation of the interaction between two CaM variants associated with congenital arrhythmia, namely N97I and Q135P, and a highly conserved CaM-binding region in RyR1 and RyR2. The structural, thermodynamic, and kinetic properties of protein-peptide interactions were assessed together with an in-depth structural and topological investigation based on molecular dynamics simulations. This integrated approach allowed us to identify amino acids that are crucial in mediating allosteric processes that enable high selectivity in molecular target recognition. Our results suggest that the ability of CaM to discriminate between RyR1 an RyR2 targets depends on kinetic discrimination and robust allosteric communication between Ca2+-binding sites (EF1-EF3 and EF3-EF4 pairs), which is perturbed in both N97I and Q135P arrythmia-associated variants.